Labor environment and its relationship with the quality of services in the district restaurants of Miraflores, Lima-Peru - Uribe Hernández, Yrene C. (2018)
To determine the level of satisfaction in restaurants of Miraflores city and the relationship between customers satisfaction and the the working environment this study was done. 150 restaurant workers and 150 consumers were surveyed. Data were collected and processed using logistic regression technique.The most outstanding result was the high level of satisfaction shown by both the internal and the external clients and the statistically significative relationship between the satusfaction level of workers with customers